Державне регулювання у сфері обігу віртуальних активів в Україні - Самсін, Р. І. (НДІ ПЗІР НАПрН України, 2022)
У статті досліджено правові норми для визначення заходів державного регулювання діяльності учасників ринку віртуальних активів в Україні. Проаналізовано норми Закону України від 17 лютого 2022 року № 2074-ІХ «Про віртуальні активи». Зазначається, що до учасників ринку віртуальних активів законодавець відніс надавачів послуг, пов’язаних з обігом віртуальних активів, і користувачів таких послуг. Послуги, пов’язані з обігом віртуальних активів, включають послуги зі зберігання або адміністрування віртуальних активів або ключів віртуальних активів, послуги з обміну віртуальними активами, послуги з передачі віртуальних активів, посередницькі послуги, пов’язані з віртуальними активами. Автор наголошує, що діяльність постачальників послуг, пов’язана з обігом віртуальних активів, дозволяється лише за умови отримання дозволу на надання послуг, пов’язаних з обігом віртуальних активів відповідного виду. Крім того, встановлено розмір плати за видачу дозволу на надання послуг, пов’язаних з обігом віртуальних активів, для резидентів і нерезидентів України та зазначено, що видача такого дозволу здійснюється відповідно до у порядку, встановленому Національною комісією з цінних паперів та фондового ринку. При цьому незрозуміло, що саме мав на увазі законодавець під «дозволом». Враховуючи, що за такий дозвіл надавачі послуг, пов’язані з обігом віртуальних активів, повинні будуть заплатити певну суму, автор припускає, що це буде «державний дозвіл на право надання послуг, пов’язаних з обігом віртуальні активи» і для його отримання надавачі послуг повинні будуть відповідати певним умовам, встановленим відповідним державним органом. Це свідчить про те, що український законодавець запроваджує ліцензування надавачів послуг, пов’язаних з обігом віртуальних активів, хоча чомусь не вживає термін «ліцензування». Цей факт також підтверджується встановленими цим Законом вимогами до осіб, які планують провадити діяльність з надання таких послуг, які за своєю суттю є «ліцензійними умовами». Вимоги до порядку отримання «дозволу» аналогічні вимогам до порядку отримання ліцензій, закріплених у Законі України від 02.03.2015 № 222-III «Про ліцензування видів господарської діяльності». Підкреслено, що діяльність постачальників послуг, пов’язаних з обігом віртуальних активів, допускається виключно за умови отримання дозволу на надання послуг, пов’язаних з обігом віртуальних активів відповідного виду. Підсумовано, що український законодавець при формуванні заходів державного регулювання діяльності учасників ринку віртуальних активів застосував ліцензування, скориставшись позитивним зарубіжним досвідом. Problem settings. The article examines the legal provisions for determining the measures of state regulation of the activities of virtual assets market participants which the Ukrainian legislator decided to apply in the sphere of circulation of such assets in Ukraine. The article analyzes the provisions of the Law of Ukraine No. 2074-IX “On Virtual Assets” dated February 17, 2022, which defines the State regulation of the virtual assets market as the implementation by the State, represented by the National Securities and Stock Market Commission and the National Bank of Ukraine, of comprehensive measures to streamline, control and supervise the virtual assets market, regulate the rules of operation of service providers related to the circulation of virtual assets, as well as measures to prevent and counteract abuses and violations in the virtual assets market. The study of legal regulation problems in the field of virtual assets was carried out such scientists as: S. Honcharenko [1, p. 152-157], A. Ovcharenko [2, p. 200-202], N. Arkhireyska, O. Kuchkova [3], V. Korneev [4, p. 40-46], O. Lyzunova [5, p. 196-199], O. Kud, M. Kucheryavenko, E. Smуchok [6, p. 33], V. Ryadinska [7, p. 152-157], A. Protsenko [8, p. 130-134], V. Polatai [9, p. 155-162] and others. The target of the research is to analyze the norms of Law No. 2074-IX to determine measures of state regulation of the activities of participants in the virtual assets market, which the Ukrainian legislator decided to apply in the sphere of circulation of such assets. Article’s main body. It is stated that the legislator has classified service providers related to the circulation of virtual assets and users of such services as participants of the virtual assets market. Services related to the circulation of virtual assets include services for the storage or administration of virtual assets or virtual asset keys, services for the exchange of virtual assets, services for the transfer of virtual assets, intermediary services related to virtual assets. The author emphasizes that the activities of service providers related to the circulation of virtual assets are allowed only subject to obtaining a permit for the provision of services related to the circulation of virtual assets of the relevant type. In addition, the amount of the fee for issuing a permit for the provision of services related to the circulation of virtual assets for residents and non-residents of Ukraine is fixed and it is noted that the issuance of such a permit is carried out in accordance with the procedure established by the National Securities and Stock Market Commission. At the same time, it is not clear what exactly the legislator meant by “permission”. Conclusions and prospects for the development. Taking into account that for such a permit providers of services related to the circulation of virtual assets will have to pay a certain amount of money, the author assumes that it will be a “state permit for the right to provide services related to the circulation of virtual assets” and in order to obtain it, service providers will have to meet certain conditions established by the relevant state body. This shows that the Ukrainian legislator introduces licensing of service providers related to the circulation of virtual assets, although for some reason does not use the term “licensing”. This fact is also confirmed by the requirements established by this Law for persons who plan to carry out activities for the supply of such services, which are essentially “licensing conditions”. The requirements for the procedure of obtaining a “permit” are similar to the requirements for the procedure of obtaining licenses enshrined in the Law of Ukraine No. 222-III “On Licensing of Economic Activities” dated March 2, 2015. It is summarized that the Ukrainian legislator in the formation of measures of state regulation of the activities of virtual assets market participants applied licensing, taking advantage of positive foreign experience.
Keywords: блокчейн; віртуальні активи; правове регулювання; заборона обігу віртуальних активів; біткойн; blockchain; virtual assets; legal regulation; prohibition of circulation of virtual assets; bitcoin